2006
DOI: 10.1080/07357900600814490
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone, High-Dose Cytarabine, and Cisplatin in Combination with Rituximab as Salvage Treatment for Patients with Relapsed or Refractory Aggressive Non-Hodgkin's Lymphoma

Abstract: We designed a multicenter Phase II trial to prospectively evaluate the efficacy and safety of the combination of rituximab with the DHAP regimen (dexamethasone, high-dose cytarabine, cisplatin) in patients who relapsed after or were resistant to a CHOP-like regimen. A total of 53 patients with relapsed or resistant aggressive B-cell NHL were analyzed. The overall response rate was 62.3 percent. With a median follow-up of 24.9 months, median overall and progression-free survivals were 8.5 and 6.7 months, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 30 publications
3
23
1
1
Order By: Relevance
“…The most significant adverse prognostic factors for response in both the whole series and the R+ group were the presence of bulky disease, primary refractory disease, an aaIPI higher than 1 at the time of R-ESHAP, as well as the administration of fewer than three cycles of R-ESHAP. Moreover, the presence of primary refractory disease and high-risk aaIPI at the time of R-ESHAP were also independent adverse prognostic factors for survival, in accordance with reports from other authors, 9,13,14,[23][24][25][26] but in contrast to the data published by Kewalramani et al, 13 who observed that the addition of rituximab to the ICE regimen seemed to overcome the adverse effects of an unfavorable IPI score. The dismal outcome of patients with primary refractory disease or with an unfavorable aaIPI at the time of relapse underlines the need for the evaluation of alternative treatments.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Ncontrasting
confidence: 57%
“…The most significant adverse prognostic factors for response in both the whole series and the R+ group were the presence of bulky disease, primary refractory disease, an aaIPI higher than 1 at the time of R-ESHAP, as well as the administration of fewer than three cycles of R-ESHAP. Moreover, the presence of primary refractory disease and high-risk aaIPI at the time of R-ESHAP were also independent adverse prognostic factors for survival, in accordance with reports from other authors, 9,13,14,[23][24][25][26] but in contrast to the data published by Kewalramani et al, 13 who observed that the addition of rituximab to the ICE regimen seemed to overcome the adverse effects of an unfavorable IPI score. The dismal outcome of patients with primary refractory disease or with an unfavorable aaIPI at the time of relapse underlines the need for the evaluation of alternative treatments.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Ncontrasting
confidence: 57%
“…A recent study reported a 92% CR rate in 24 patients with previously untreated mantle cell NHL with RDHAP [20]. Mey et al [21] performed a trial of RDHAP that focused only on patients with relapsed aggressive NHL and patients could not have received prior rituximab. The RDHAP regimen differed from this trial in that the rituximab was given d1 of each of a planned four cycles.…”
Section: Discussionmentioning
confidence: 99%
“…30% (6/20) received etoposide in addition to CHOP (as CHOEP or EPOCH) [9,[23][24][25][26], with or without intrathecal chemotherapy. 5.0% (1/20) received CHOP alternating with DHAP (dexamethasone, high dose cytarabine, cisplatin) [28,29]. There were no significant differences in primary systemic therapies received between the two groups (P 5 0.82, Table I).…”
Section: Baseline Characteristicsmentioning
confidence: 99%